Yield Evaluation Of Cultivated Drought Tolerant Rice Varieties In Bangladesh (SAARC Journal of Agriculture, 2024)
An experiment was conducted with seven drought tolerant rice varieties i.e., Binadhan-17, Binadhan-19, BRRI dhan56, BRRI dhan57, BRRI dhan66, BRRI dhan71 and BRRI dhan83 were used as plant materialism. Boro season during December 2022-May 2023 to evaluate the yield performance at the reproductive stage as well as disclose the inherent variability of the varieties for yield and yield attributing traits following a randomized complete block design with three replications. Significant variation (p